NILAI GAPURA PANCA WALUYA DALAM WAWACAN BABAD SUMEDANG SEBAGAI PENGUATAN KARAKTER PESERTA DIDIK DALAM PEMBELAJARAN SASTRA - Nur Fadilah, Fitri; Sukmana, Ece; Kuswara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education is an essential aspect of education because it aims not only to develop students’ intellectual abilities but also to strengthen moral values, social responsibility, and cultural identity. Traditional literary works can serve as a medium for character development because they contain local wisdom and life values inherited from society. This study aims to analyze the ethnopedagogical values of Gapura Panca Waluya in the Sundanese traditional literary work Wawacan Babad Sumedang and to explain its relevance as a source of character strengthening for students in literary learning. This research employed a qualitative approach with a descriptive analytical method. The data source was the text of Wawacan Babad Sumedang manuscript variant Plt-29-Peti-121 by Abdoerachman. Data were collected through documentation studies and textual analysis by identifying, interpreting, and categorizing cultural values based on the concepts of cageur, bageur, bener, pinter, and singer. The results showed that Wawacan Babad Sumedang contains significant ethnopedagogical values representing the ideal Sundanese human character (jalma anu masagi). The value of cageur reflects self-control and inner balance, bageur represents social concern and respect, bener emphasizes integrity and responsibility, pinter illustrates intelligence and wisdom, while singer reflects creativity and adaptability. These findings indicate that traditional Sundanese literature has relevance as a source of character education and can be integrated into literary learning based on local cultural values.